Chaos Control and Synchronization of a New Fractional Laser Chaotic System - Eshaghi, Shiva; Kadkhoda, Nematollah; İnç, Mustafa (Springer Basel Ag, 2024)
In this article, we introduce a new fractional laser chaotic system derived from the Lorenz-Haken equations. We investigate the complex dynamics of the proposed system consisting chaos, stability, control and synchronization of chaos. Moreover, we numerically reveal the nonlinear dynamics of the fractional laser chaotic system through the phase portraits, time histories and bifurcation diagrams. Also, we indicate the chaotic behaviors of the system by means of Lyapunov exponents, bifurcation diagrams versus all parameters along the state variables, phase portraits and time histories with different trajectories and initial conditions. The necessary conditions to eliminate the chaotic vibration of the system are obtained via the feedback control procedure. Meanwhile, a synchronization mechanism based on the feedback control technique is achieved for coupled fractional laser chaotic systems. Furthermore, we show that the fractional derivative order is very effective on reducing the irregular and chaotic behaviors of the system.
Keywords: Fractional laser chaotic system; Synchronization; Control; Chaotic behavior